REVIEW 5 TAHUN KARAKTERISTIK KLINIS PASIEN BENDA ASING INTRAOKULAR DI PMN RS MATA CICENDO - Desrina; Virgana, Rova; Kartasasmita, Arief S.; Iskandar, Erwin; Ihsan , Grimaldi; Widyanatha, Made Indra (Oftalmologi : Jurnal Kesehatan Mata Indonesia, 2023)
Introduction: Intraocular foreign bodies (IOFBs) are defined as intraocularly retained, unintentional projectiles that require urgent diagnosis and treatment to prevent blindness or globe loss. IOFBs account for 18–41% of open globe injuries, and frequently cause severe visual loss in patients with ocular trauma.The purpose of this study are is to describe the characteristics of open-globe injuries with posterior segment intraocular foreign bodies (IOFB). Subject and Methods: Retrospective data of all patients with posterior segment IOFBs from 2017 to 2022 was conducted. Data including demographics, mechanism of injury, type of IOFB, method of diagnosis, presenting examination, medical and surgical treatment, visual outcomes, and complications were recorded. Result: There were 39 patients (eyes) with IOFB, 38 (97,4%) were male, 10 (25,6%) were 46-55 years old. The most common IOFB occurred at workplace 30 patient (85,7%), 29 (74,3%) were insuranced, surgery were performed 1- 4 days in 15 (38,5%. The most Ocular trauma score were 3 (38,5%) and 2 (35,9%) initial VA were light perception – hand movement (25 or 64,1%), final VA with BCVA were > 20/40 (30,8%) patients and 6/60-6/15 (25,6%). The posterior segment IOFB (51,3%, metallic IOFB 25 (61,5%). Cataract 74,3% and Endophthalmitis (20,5%) were found in initial examination patient with IOFB (13 or 37,1%). Late complication in post surgery IOFB patient was glaucoma 14,4%. Conclusions: The IOFB occurred most commonly in adults, men, at the workplace. The IOFB mostly was metallic, found in the posterior segment. Cataract and endoftalmitis were common in initial finding IOFB patients.